Analisis Faktor-Faktor yang Memengaruhi Niat Beli pada Makanan Restoran Jepang Bersertifikat Halal MUI - Muhammad Delfi Akbar Maulana; Siti Nursyamsiah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of subjective norms, perceptions of behavioral control, religiosity, and attitudes on Muslim consumers' purchase intentions on food from MUI-certified Japanese restaurants. The population in this study refers to all Muslim people in Indonesia who know Japan restaurant food is halal certified by the MUI with a total sample of 170 respondents and 42 respondents for the pre-test. The sampling method in this study used a non-probability sampling method with purposive sampling and convenience sampling because sampling was carried out by taking subjects based on certain criteria not based on strata, random or region and distributed based on the convenience of the researcher. This study uses a quantitative approach by distributing questionnaires using Google forms online through social media such as WhatsApp, Line and Instagram. This study uses structural equation model analysis or SEM (Structural Equation Modeling) which is processed using SmartPLS software. The results of data analysis in this study indicate that subjective norms and perceptions of behavioral control have a positive and significant effect on purchase intentions. Religiosity has a positive and significant effect on attitudes. And there is no influence between religiosity and attitude towards purchase intention.